2011
DOI: 10.1158/1078-0432.ccr-11-0650
|View full text |Cite
|
Sign up to set email alerts
|

MK-1775, a Novel Wee1 Kinase Inhibitor, Radiosensitizes p53-Defective Human Tumor Cells

Abstract: Purpose Radiotherapy is commonly used to treat a variety of solid tumors. However, improvements in the therapeutic ratio for several disease sites are sorely needed leading us to assess molecularly targeted therapeutics as radiosensitizers. The aim of this study was to assess the wee1 kinase inhibitor, MK-1775, for its ability to radiosensitize human tumor cells. Experimental Design Human tumor cells derived from lung, breast and prostate cancers were tested for radiosensitization by MK-1775 using clonogenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
174
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 27 publications
5
174
0
Order By: Relevance
“…Since the G2 phase of the cell cycle provides a pause during which post-replication errors and breaks are corrected, its premature termination by Wee1 inhibition might promote the mitotic death of cells failing to complete repair. 12,25,35 This could be particularly relevant to pancreatic cancers, given their high degree of genomic instability. However, there was no significant single agent activity in our PDX models, which is consistent with the low response rate of MK-1775 (AZD1775) in human clinical trials.…”
Section: Mk-1775 (Now Azd1775mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the G2 phase of the cell cycle provides a pause during which post-replication errors and breaks are corrected, its premature termination by Wee1 inhibition might promote the mitotic death of cells failing to complete repair. 12,25,35 This could be particularly relevant to pancreatic cancers, given their high degree of genomic instability. However, there was no significant single agent activity in our PDX models, which is consistent with the low response rate of MK-1775 (AZD1775) in human clinical trials.…”
Section: Mk-1775 (Now Azd1775mentioning
confidence: 99%
“…11 Preclinical studies have shown that Wee1 inhibition can sensitize cells to mitotic catastrophe following exposure to DNA damaging agents, and several studies are ongoing to test this possibility this in the clinic. 7,[12][13][14][15] Wee1 has an additional role as a Cdk2 kinase, which is relevant to the development of cancer treatment strategies that incorporate Wee1 inhibitors. 16,17 The activation of Cdk2 promotes origin firing during S-phase, and regulates the overall timing of DNA replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Wee1 potentiates DNA-damaging chemotherapeutics and radiotherapy and has cytotoxic effects as a single agent (19)(20)(21)(22). The consensus view is that Wee1 inhibition facilitates tumor cell killing through G 2 /M checkpoint inactivation, which would catalyze mitotic catastrophe (23)(24)(25).…”
mentioning
confidence: 99%
“…More recently, inhibition of Wee1, another kinase that promotes G2/M checkpoint activation in response to radiation, has emerged as a potential therapeutic strategy [17]. As with ATM inhibitors, a number of studies have indicated that the effects of ATR or Wee1 inhibitors are more pronounced in p53 defective contexts [18,19].…”
Section: Cell Cycle Checkpoint Inhibitorsmentioning
confidence: 99%